1972
DOI: 10.1139/m72-153
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the mode of action of the alpha toxin of Staphylococcus aureus "Wood-46"

Abstract: Further evidence has been obtained which supports the view that alpha toxin from Staphylococcus aureus "Wood 46" is a protease which requires activation by erythrocyte membrane proteases. Rabbit erythrocyte antiprotease prepared in mice inhibited degradation of rabbit ghosts by the toxin. Supernatant fluid of toxin-treated ghosts incubated with EDTA and then passed through a column of Sephadex G-75 yielded a fraction which was hemolytic and proteolytic. These activities were both neutralized by alpha antitoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Purified S-lysin was also kindly sent to us by Dr Arnold Kreger. Haemolysin titrations were performed as described by Wiseman and Caird (1972). Buffers were prepared according to Gomori (1955) and, where required, 0 .…”
Section: Methodsmentioning
confidence: 99%
“…Purified S-lysin was also kindly sent to us by Dr Arnold Kreger. Haemolysin titrations were performed as described by Wiseman and Caird (1972). Buffers were prepared according to Gomori (1955) and, where required, 0 .…”
Section: Methodsmentioning
confidence: 99%
“…Haemolytic titrations of gamma lysin were performed with human red cells as described by Wiseman & Caird (1972). Human blood (Rh+, group 0) obtained from the Canadian Red Cross in Winnipeg was stored in acid-citrate-dextrose solution as supplied.…”
Section: Methodsmentioning
confidence: 99%
“…Proteolytic activity of cultures in some experiments was determined as described by Wiseman & Caird (1972).…”
Section: Methodsmentioning
confidence: 99%
“…Both the proteolytic and haemolytic activities of activated toxin have been shown to be neutralised by a-antitoxin (Wiseman and Caird, 1972). It has also been suggested that this a-'' protoxin " is activated by erythrocyte proteases and that the level of protease activity in red cells of various species explains their differing sensitivity to the toxin.…”
mentioning
confidence: 99%
“…Haemolytic activity was measured according to the method outlined by Wiseman and Caird (1972). Proteolytic activity was assayed according to the technique described by Hummel (1959) in which p-toluenesulphonyl-L-arginine methylester (TAME) was used as a substrate.…”
mentioning
confidence: 99%